Clinical Application of Genetic Prediction in the Management of CAD - Robert Roberts,; Jacques Fair, (International Journal of Innovative Research in Medical Science, 2021)
Sequencing of the human genome followed by the HapMap project made possible the unbiased genome-wide association studies that led to the discovery of hundreds of genetic risk variants predisposing to CAD. The total genetic risk for CAD can be expressed in a single number based on the number of variants inherited. A GRS derived from genotyping with microarrays containing these risk variants has been evaluated in over 1 million individuals. Risk stratification for CAD based on the GRS was shown to be superior to conventional risk factors. Placebo-controlled clinical trials showed individuals with high genetic risk had a 40-50% reduction in cardiac events with a favorable lifestyle, and cholesterol-lowering drugs. The risk of CAD based on conventional risk factors such as hypertension are age-dependent, occurring primarily in the sixth or seventh decade which is too late for primary prevention. The GRS is independent of age and can be determined at birth if needed. Incorporation of the GRS into clinical practice would transform the primary prevention of CAD, the number one killer.